Development of a standard operating procedure for the DCFH2-DA acellular assessment of reactive oxygen species produced by nanomaterials. (24th July 2022) - Boyles, Matthew; Murphy, Fiona; Mueller, William; Wohlleben, Wendel; Jacobsen, Nicklas Raun; Braakhuis, Hedwig; Giusti, Anna; Stone, Vicki
Abstract: Improved strategies are required for testing nanomaterials (NMs) to make hazard and risk assessment more efficient and sustainable. Including reduced reliance on animal models, without decreasing the level of human health protection. Acellular detection of reactive oxygen species (ROS) may be useful as a screening assay to prioritize NMs of high concern. To improve reliability and reproducibility, and minimize uncertainty, a standard operating procedure (SOP) has been developed for the detection of ROS using the 2′, 7′-dichlorodihydrofluorescein diacetate (DCFH2 -DA) assay. The SOP has undergone an inter- and intra-laboratory comparison, to evaluate robustness, reliability, and reproducibility, using representative materials (ZnO, CuO, Mn2 O3, and BaSO4 NMs), and a number of calibration tools to normalize data. The SOP includes an NM positive control (nanoparticle carbon black (NPCB)), a chemical positive control (SIN-1), and a standard curve of fluorescein fluorescence. The interlaboratory comparison demonstrated that arbitrary fluorescence units show high levels of partner variability; however, data normalization improved variability. With statistical analysis, it was shown that the SIN-1 positive control provided an extremely high level of reliability and reproducibility as a positive control and as a normalization tool. The NPCB positive control can be used with a relatively high level of reproducibility, and in terms of the representative materials, the reproducibility CuO induced-effects was better than for Mn2 O3 . Using this DCFH2 -DA acellular assay SOP resulted in a robust intra-laboratory reproduction of ROS measurements from all NMs tested, while effective reproduction across different laboratories was also demonstrated; the effectiveness of attaining reproducibility within the interlaboratory assessment was particle-type-specific.